POLITICAL CHANGING FOR PRIME MINISTER OF JAPAN - Osamu Ryoichi (UNISSULA, 2021)
The prime minister of Japan (日本国内閣総理大臣, Nihon-koku naikaku sōridaijin, or shushō (首相)) (informally referred to as the PMOJ) is head of the government of Japan, the chief executive of the National Cabinet and the commander-in-chief of the Armed Forces of Japan; he is appointed by the emperor of Japan after being designated by the National Diet and must enjoy the confidence of the House of Representatives to remain in office. He is the head of the Cabinet and appoints and dismisses the other ministers of state. The literal translation of the Japanese name for the office is Minister for the Comprehensive Administration of (or the Presidency over) the Cabinet. The current prime minister of Japan is Yoshihide Suga. On 14 September 2020, he was elected to the presidency of the governing Liberal Democratic Party (LDP). After being confirmed in the Diet, he received an invitation from Emperor Naruhito to form a government as the new prime minister, and took office on 16 September 2020. Japan's parliament has elected Yoshihide Suga as the country's new prime minister, following the surprise resignation of Shinzo Abe. After winning the leadership of the governing party earlier this week, Wednesday's vote confirms the former chief cabinet secretary's new position. It happened because the needed of political interest for Japan.